Association between depression and HbA1c levels in the elderly population with type 2 diabetes mellitus during COVID-19 pandemic - Zahra, Zulfa; Ramadhani, Cut T.; Mamfaluti, Teuku; Pamungkas, Subhan R.; Firdausa, Sarah (Narra Sains Indonesia, 2022)
Diabetes mellitus is a chronic progressive disease affecting the metabolic hormonal system and its prevalence in the elderly population is high. Depression is one of the psychiatric disorders in diabetic patients in particular during the coronavirus disease 2019 (COVID-19) pandemic. People with depression are more susceptible to leading an unhealthy lifestyle; therefore, depression and diabetes have a negative influence on life quality and aggravate complications and symptoms. The aim of this study was to determine the association between depression and hemoglobin A1c (HbA1c) levels in elderly with type 2 diabetes mellitus patients. A cross-sectional study was conducted where a total of 42 diabetic patients from the Puskesmas Belakang Padang, Batam of Indonesia was recruited. The HbA1c level, the main determinant of optimum glycemic control, was measured using ion-exchange high-performance liquid chromatography while the level of depression was assessed using Geriatric Depression Scale-15 (GDS-15). The association between depression and HbA1c levels was analyzed using the chi-squared test. Our study found that that 69% of the elderly with diabetes experienced a depression, classified as mild (40.5%), moderate (21.4%) and severe (7.1%). There were 61.9% of the subjects had poor HbA1c control. Our data suggested that the depression level was associated with HbA1c (p=0.002). In conclusion, there is a significant association between depression and HbA1c levels in the elderly with type 2 diabetes mellitus.